The influence of parent-initiated motivational climate on adolescent golfers` flow experiences: the mediating role of basic psychological needs - Sim, Y.; Kwon, S.; Lee, D. (Perceptual and Motor Skills, 2025)
The aim of this study was to investigate the roles of adolescent golf athletes` perceptions of (a) parent-initiated motivational climate and (b) their satisfaction of basic psychological needs in predicting their self-reported flow state. Participants were 429 adolescent golfers (Males = 203, Females = 226) who were registered with the Korean Sport and Olympic Committee and who completed surveys measuring these constructs. To verify the structural validity of the measurement tools, descriptive statistics, inference analysis, correlational analysis, structural equation modeling, and confirmatory factor analysis were employed. Also, in structural equation modeling, we examined the mediating effect of satisfying psychological needs in the relationship between parent-initiated motivational climate and flow state. Results showed that these participants` perceptions of their task-involved, parent-initiated motivational climate was positively related to their perceptions of their basic psychological needs. Basic psychological needs were significantly and positively related to flow. However, perceived parent-initiated motivational climate was not significantly related to flow. Therefore, athletes` perception of their basic psychological needs completely mediated the relationship between parent-initiated motivational climate and flow. The task-involved, parent-initiated motivational climate perceived by adolescent golf athletes predicted their increased self-report of flow through satisfaction of basic psychological needs. The analysis verified that adolescent golfers` perceptions of a task-involved, parent-initiated motivational climate may have contributed to achieving perceived flow and, presumably, peak performance. Consequently, these findings highlight the crucial role of parental involvement in creating an optimal environment for young athletes` performance.